Medical device regulation (MDR) in health technology enterprises - perspectives of managers and regulatory professionals - Juhamatti Huusko; Ulla-Mari Kinnunen; Kaija Saranto (BMC, 2023)
Abstract Background In the European Union (EU), there are over half a million medical devices, varying from pacemakers to software. Medical devices play an important role in health care as they are used in diagnosis, prevention, monitoring, prediction, prognosis, treatment, or to alleviate disease. Medical devices are regulated in the EU by the Medical Device Regulation (MDR), which came into force on 25 April 2017 and into application on 26 May 2021. The demand for regulation arose from the need to establish a transparent, robust, predictable, and sustainable regulatory framework. This study aims to examine how the managers and regulatory professionals in health technology enterprises perceived the application of the MDR and what were their information needs regarding the MDR. Methods A link to an online questionnaire was sent to 405 managers and regulatory professionals representing health technology enterprises in Finland. The study included 74 respondents. Descriptive statistics were used to describe and summarise the characteristics of the dataset. Results Information related to the MDR was fragmented and the necessary information was sought from multiple information sources, while the Finnish Medicines Agency (Fimea) was regarded as the most important source of information and training provider. To some extent, the managers and regulatory professionals expressed their dissatisfaction with the performance of Fimea. The managers and regulatory professionals were not very familiar with the ICT systems provided by the EU. The size of an enterprise affected how many medical devices it manufactures and generally affected the views about the MDR. Conclusions The managers and regulatory professionals understood the role of the MDR regarding the safety and transparency of medical devices. The available information regarding the MDR did not properly fit the needs of users and there seemed to be a gap in information quality. The managers and regulatory professionals had some difficulties understanding the available information. Based on our findings, we believe it is paramount to evaluate the challenges faced by Fimea and how it could improve its performance. To some extent, the MDR is regarded as a burden for smaller enterprises. It is important to highlight the benefits of ICT systems and to develop them to better meet the information needs of enterprises.